Personal Branding "Gemoy"Prabowo (Case Study On The Tiktok Account @Partai Gerindra) - Aghisty Firan Marenza; Yanto Yanto; Martha Heriniazwi Dianti (Jurnal Multidisiplin Dehasen (MUDE), 2024)
Personal Branding is described as a process or effort to build a unique, strong and relevant self-image in the minds of other people. This involves identifying and building on our personal strengths, abilities, and uniqueness as characteristics that differentiate us from others. One of the social media that reflects Prabowo's branding as "gemoy" is the tiktok account @Partai Gerindra. This research aims to dig deeper into the process of forming Gemoy Prabowo's Personal Branding, especially related to the 'gemoy' image that is seen in his public interactions and increasing popularity and having a significant impact on Tiktok social media. The type of research method used in this thesis is descriptive qualitative research. The importance of this research lies in an in-depth understanding of the relationship between Personal Branding of political figures and public perception of their political image. The theory used is Peter Montoya's theory where Personal Branding marketing is the process of building and strengthening a person's personal image and reputation in the minds of other people. There are eight processes for forming Personal Branding owned by Peter Montonya, namely: 1. Specialization (The Law of Specialization), 2. Leadership (The Law of Leadership), 3. Personality (The Law of Personality), 4. Difference (The Law of Distinctiveness) , 5. Visibility (The Law of Visibility), 6. Unity (The Law of Unity), 7. Firmness (The Law of Peristence), 8. Good name (The Law of Goodwill).The results of the research and discussion are concluded as follows from the results of research conducted on Gemoy Prabowo's Personal Brandingon the Gerindra Party TikTok account, that this Personal Branding has succeeded in creating a strong and positive image among social media users. Gemoy Prabowo was able to build a unique and attractive personal identity by introducing the Gerindra Party to the public via the TikTok platform.